(untitled) (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2020)
School Action Research entitled "Implementation of Individual Supervision Techniques in Islamic Religious Education Teachers as Implementation of Supervisory Work is a study conducted to find out the implementation of individual supervision techniques of Islamic religious education teachers, implementation of Islamic education supervisors’ performance and the effect of implementing individual Religious Education Teacher supervision techniques. Islam as an implementation of supervisory work. As for the goal of the research is the process of implementing individual teacher supervision technique of Islamic education, the implementation performance of Trustees Islamic education and influence the implementation of individual supervision on engineering education teachers of Islamic religion as the implementation of the work kepengawasan.The research is the research field where researchers use observational techniques through classroom visits and interviews. The results of this study found that the school principal/supervisor had socialized supervision activities, but had not been intense in the school, the teacher’s understanding in this case the Islamic religious education teacher did not fully understand the education supervision because the teacher was not usually supervised and teachers at YAKMI Islamic Elementary School in terms of PBM supervision, they are very committed to advancing their schools so they can be equal with other schools, one way is through education supervision where supervision can see shortcomings in the PBM process.